PENERAPAN METODE PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII.D SMP NEGERI 40 PEKANBARU TAHUN 2017 - Hidayati, Hidayati; Imrialdi, Imrialdi (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2018)
In SMP 40 Pekanbaru, many problems of students in the learning process IPS caused by external factor as the influence of friends environment and internal factors as learning approaches, methods, media or learning tools are used. These problems must be repaired because in addition to results in student learning outcomes that are still below the Minimum Completeness Criteria (KKM), the learning of Social Sciences (IPS) also has a central role in the intellectual development of social, emotional students and is a supporting success in studying of the other fields of study. The reseacrh was designed with the class action research by the Kemmis and McTaggart models in the form of spiral cycles. The results showed that the application of role palying learning methods have improved IPS learning outcomes of VIII.D graders at SMP 40 Pekanbaru in the years of 2017th with an average value class and the percentage of KKM achievment during the pre actions was 69.3 and 36%, in the cycle I was 78.6 and 69%, and in the cycle II it became 85.1 and 95%.